2013
DOI: 10.19173/irrodl.v14i4.1548
|View full text |Cite
|
Sign up to set email alerts
|

Learning in a small, task–oriented, connectivist MOOC: Pedagogical issues and implications for higher education

Abstract: FSLT12 was an open and free professional development opportunity for people moving into HE teaching. It was a small course (200 participants registered from 24 countries) which was focused on introducing HE teaching skills, and, uniquely, to deliberately integrate open academic practice as a vital part of professional development for HE teachers. A qualitative, case-study approach was used in the research, based on surveys, interviews, and social media, to provide evidence about how people learned in this cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 9 publications
4
70
0
4
Order By: Relevance
“…In a case study of FSLT12, Mackness et al (2013) noted that participants reported encountering challenges similar to those reported by other studies of connectivist learning including adapting to distributed learning environments, collaborative learning styles, managing online identities, and overcoming the inherent uncertainty of emergent learning. However, the combination of peer mentorship and task-based learning strategies proved a successful means of supporting novice participants.…”
Section: Task-basedmentioning
confidence: 65%
See 3 more Smart Citations
“…In a case study of FSLT12, Mackness et al (2013) noted that participants reported encountering challenges similar to those reported by other studies of connectivist learning including adapting to distributed learning environments, collaborative learning styles, managing online identities, and overcoming the inherent uncertainty of emergent learning. However, the combination of peer mentorship and task-based learning strategies proved a successful means of supporting novice participants.…”
Section: Task-basedmentioning
confidence: 65%
“…However, this approach has been criticized as operating on regressive pedagogical principles (Guardia, Maina, & Sangra, 2013;Hollands & Tirthali, 2014;Rodriguez, 2012;Stacey, 2014). Mackness, Waite, Roberts, and Lovegrove (2013) note: "The pedagogical approach of the massive xMOOCs is currently under scrutiny since some research suggests that large-scale lectures and demonstrations do not support learner understanding" (p. 154). From the perspective of socialconstructivism, the xMOOC model conflicts with research that has demonstrated the importance of social engagement, applied practice, and formative feedback for effective online learning.…”
Section: Content-based Community and Task-based Network-basedmentioning
confidence: 99%
See 2 more Smart Citations
“…This has implications for diversity (Mackness, Waite, Roberts & Lovegrove, 2013). As the numbers drop, diversity decreases and it becomes increasingly difficult for some learners to sustain their weak connections.…”
Section: Literature That Informs This Researchmentioning
confidence: 99%